أمثلة مسألة توزيع الكتل الترابية متعددة الأنواع باستخدام البرمجة الخطية - جراد فايز (Latakia University Journal -Engineering Sciences Series, 2017)
تمثل أعمال نقل التربة جزءاً أساسياً من أعمال المشاريع الهندسية ، كما تمثل تكلفة بنود تلك الأعمال الجزء الأكبر في مشروعات السدود والطرق والمطارات. ولما كانت التكلفة تعتمد على مجموعة من العوامل المؤثرة في تلك التكلفة فان التكلفة من المسائل الهامة في إدارة المشاريع. تناول هذا البحث عرضاً موجزاً لمختلف الطرق التي استخدمت في حساب تكلفة أعمال التربة والعوامل المؤثرة على هذه التكلفة. تم تطوير النماذج الرياضية القديمة بحيث يمكنها التعامل مع وجود أكثر من نوع من التربة في أماكن الحفر والردم كما عالج النموذج المطور مشكلة نقل التربة عند تواجد أنواع من التربة في أماكن الحفر لابد من ترحيلها لأنها غير صالحة للردم بحيث تم استخدام البرمجة الخطية لصياغة النموذج الرياضي وتكوين دالة الهدف والشروط المقيدة مع الأخذ بعين الاعتبار جميع الحالات التي يمكن تواجدها في المشروع. تم إعداد برنامج حاسوبي لتكوين المشكلة بشكل قياسي واستخدام برنامج (LINDO) لحل النموذج المشكل من البرنامج الحاسوبي وإعطاء الحل الأمثل. Earthmoving is the process of moving and processing soil from one location to another to alter an existing land surface into a desired configuration. Highways, dams, and airports are typical examples of heavy earthmoving projects. Over the years, construction managers have devised ways to determine the quantities of material to be moved from one place to another. Various types of soil (soft earth, sand, hard clay, …, etc.) create different level of difficulty of the problem. Earthmoving problem has traditionally been solved using mass diagram method or variety of operational research techniques. However, existing models do not present realistic solution for the problem. Multiple soil types are usually found in cut sections and specific types of soil are required in fill sections. Some soil types in cut sections are not suitable to be used in fill sections and must be disposed of. In this paper a new mathematical programming model is developed to find-out the optimum allocation of earthmoving works. In developing the proposed model, different soil types are considered as well as variation of unit cost with earth quantities moved. Suggested borrow pits and/or disposal sites are introduced to minimize the overall earthmoving cost. The proposed model is entirely formulated using the programming capabilities of VB6 while LINDO is used to solve the formulated model to get the optimum solution. An example project is presented to show how the developed model can be implemented.